2012
DOI: 10.1097/ta.0b013e31826fc85f
|View full text |Cite
|
Sign up to set email alerts
|

Repeated computed tomographic scans in transferred trauma patients

Abstract: Diagnostic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 21 publications
3
43
1
1
Order By: Relevance
“…[7][8][9]14,17 Of those studies which assessed indications for repeat imaging, Gupta et al 18 and Sung et al 19 reported similar findings to this study, namely that clinical need was the most commonly cited reason for a repeat CT scan. [7][8][9]14,17 Of those studies which assessed indications for repeat imaging, Gupta et al 18 and Sung et al 19 reported similar findings to this study, namely that clinical need was the most commonly cited reason for a repeat CT scan.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…[7][8][9]14,17 Of those studies which assessed indications for repeat imaging, Gupta et al 18 and Sung et al 19 reported similar findings to this study, namely that clinical need was the most commonly cited reason for a repeat CT scan. [7][8][9]14,17 Of those studies which assessed indications for repeat imaging, Gupta et al 18 and Sung et al 19 reported similar findings to this study, namely that clinical need was the most commonly cited reason for a repeat CT scan.…”
Section: Discussionsupporting
confidence: 63%
“…In approximately one in five cases of repeat CT scanning, the clinical justification was not apparent from retrospective assessment of the available medical records. 4,7,13,[15][16][17][18] This study noted that CT scans were repeated for predominantly clinical reasons. Hill et al 6 found that 48% of patients transferred to their facility underwent repeat imaging, although it is unclear what proportion of this was accounted for by CT as they also included plain radiographic studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians want access to these studies and results, for accurate interpretation and diagnoses [13], but often, they are difficult to obtain in a timely manner [4]. This lack of access may result in additional imaging [5], thereby increasing radiation exposure of the patient [6] and creating avoidable costs [7,8]. In addition, searching for studies from other sources wastes provider time [9–12] and delays treatment [13].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21] This includes 24/7 radiology technologists and radiologists in the emergency room, operating rooms, and hospital wards. [12][13][14][15][16][17][18][19][20][21] This includes 24/7 radiology technologists and radiologists in the emergency room, operating rooms, and hospital wards.…”
Section: Imaging Development and Support: Radiologymentioning
confidence: 99%